THE TRADITION OF THANKSGIVING IN THE MINAHASA COMMUNITY, NORTH SULAWESI: A REVIEW FROM THE HAPPINESS THEORY PERSPECTIVE: Tradisi Pengucapan dalam Masyarakat Minahasa, Sulawesi Utara: Tinjauan dari Teori Kebahagiaan - Stephanie Raqueen Inaray; Marselius Tondok (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The tradition of Thanksgiving in the Minahasa community, North Sulawesi, known as